Pengaruh Dewan Komisaris, Dewan Direksi, dan Komite Audit terhadap Kinerja Keuangan - Rina Adelina Christia Heldrika Simanullang; Asep Muslihat (AKUA: Jurnal Akuntansi dan Keuangan, 2026)
This study aims to empirically examine whether the board of commissioners, the board of directors, and the audit committee influence the financial performance of companies in the metals and minerals industry listed on the Indonesia Stock Exchange. Using secondary data sourced from companies’ annual reports, this study employs a quantitative methodology. 7 metal and mineral industry companies listed on the Indonesia Stock Exchange from 2020 to 2024 were selected as the research sample. Multiple linear regression analysis was used as the data analysis method in this scientific study. The research findings partially indicate a negative effect of the board of directors on financial performance, revealing that as the number of board members increases, financial performance tends to decline due to coordination complexities. However, the audit committee and the board of commissioners do not have a significant effect on financial performance. The board of commissioners, the board of directors, and the audit committee have a combined effect on financial performance, indicating that the management and oversight functions of these three governance bodies work together to achieve the company’s financial performance.